ANALISIS KELEMBAGAAN PENGENDALIAN HAMA TERPADU MENDUKUNG AGRIBISNIS KOPI RAKYAT DALAM RANGKA OTONOMI DAERAH - -, SAPTANA; TARIGAN, HERLINA; SETIANTO, ADI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005, 2012)
Integrated Pest Management Program (IPM) that is strategic operational measure. In the micro farm level, IPM operational measure can be answered both capital problem in the farm level and international commodity coercion on environmental and food safety consumption simultaneously. That paper objective to analysis : (1) historical government policy on IPM related the decentralization of development; (2) performance, constrain, and prospective IPM program in the decentralization era; (3) comparative farming performance IPM cooperator, inter success farms group and least success farms group; (4) factors that affected dissemination and adoption IPM technology; (5) synopsis on IPM sustainable institution in the decentralization era; and (6) to formulate police IPM sustainable development alternative supporting small coffee agribusiness in the decentralization era. Rates of participation of the IPM program participants varied among activities, i.e., planning, implementation, monitoring and evaluation. Low participation rate was found in planning, that of implementation was high, while that of monitoring and evaluation was low to moderate. Program explanation during the planning stage was not properly carried out. The other weaknesses were management of post harvest, processing, and marketing. After the IPM program average net benefits from coffee bean and additional in-rows plants were to increase, respectively. Economic factors positively affecting IPM technology adoption were: (1) decreasing costs of inputs (fertilizers and pesticides); (2) improving farmers’ income through higher yield and better quality; (3) improving stability and continuity of farmers’ income due longer harvest and productive periods, and the products were sold periodically. In the future, development of IPM program for smallholding coffee plantation is based on the clear vision, namely IPM technology for improving rural people welfare. This vision has to replace the old vision, namely IPM technology is created just to show that the researchers are able to show their ability in developing technology. Therefore, in the future IPM development has to implicate directly to improved competitive economy and rural people welfare.
Keywords: Institutional, Integrated Pest Management, Agribusiness, Coffee, Regional Autonomy